TMT Involvement in Family Firm’s Growth-Related Strategic Decision-Making: A Dynamic Capability Perspective - Torchia, Mariateresa; Calabrò, Andrea; Walther, Axel (Management international / International Management / Gestiòn Internacional, 2021)
Drawing on the dynamic capabilities perspective we examine the relationship between top management team’s (TMT’s) involvement in strategic decision-making and family firm growth. Additionally, we posit that this relationship varies by firm’s prioritized growth mode, internal dynamism and environmental dynamism. Data from 357 German family firms suggest that family firms with highly involved TMTs are less likely to grow in contexts of high internal dynamism, whereas growth benefits from highly involved TMTs in context of environmental dynamism.